2020
DOI: 10.1038/s41467-020-15611-3
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric regulation accompanied by oligomeric state changes of Trypanosoma brucei GMP reductase through cystathionine-β-synthase domain

Abstract: Guanosine 5′-monophosphate reductase (GMPR) is involved in the purine salvage pathway and is conserved throughout evolution. Nonetheless, the GMPR of Trypanosoma brucei (TbGMPR) includes a unique structure known as the cystathionine-β-synthase (CBS) domain, though the role of this domain is not fully understood. Here, we show that guanine and adenine nucleotides exert positive and negative effects, respectively, on TbGMPR activity by binding allosterically to the CBS domain. The present structural analyses rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…Some enzymes with the CBS domain are known to regulate activity through purine nucleotide binding to this domain [44]. A recent study demonstrated that TbGMPR has an oligomeric conformation with allosteric regulation via the CBS domain [45]. The binding of guanine nucleotides (GTP or GMP) and adenine nucleotides (ATP) to an allosteric regulatory site, formed at the cleft between the catalytic and CBS domains, leads to positive and negative regulation, respectively, accompanied by changes in the multimeric enzyme structure (Fig.…”
Section: Guanine Nucleotide Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…Some enzymes with the CBS domain are known to regulate activity through purine nucleotide binding to this domain [44]. A recent study demonstrated that TbGMPR has an oligomeric conformation with allosteric regulation via the CBS domain [45]. The binding of guanine nucleotides (GTP or GMP) and adenine nucleotides (ATP) to an allosteric regulatory site, formed at the cleft between the catalytic and CBS domains, leads to positive and negative regulation, respectively, accompanied by changes in the multimeric enzyme structure (Fig.…”
Section: Guanine Nucleotide Metabolismmentioning
confidence: 99%
“…The binding of guanine nucleotides (GTP or GMP) and adenine nucleotides (ATP) to an allosteric regulatory site, formed at the cleft between the catalytic and CBS domains, leads to positive and negative regulation, respectively, accompanied by changes in the multimeric enzyme structure (Fig. 5) [45]. Specifically, TbGMPR with a "relaxed octamer" conformation in the apo form is transformed into an active "twisted octamer" by binding to GTP or GMP, while the binding of ATP disrupts the octamer structure to dissociate into two inactive tetramers.…”
Section: Guanine Nucleotide Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Trypanosoma brucei GMPR is the only known GMPR structure that contains CBS domains (Imamura et al, 2020). The presence of CBS domains in GMPRs is unusual.…”
Section: X-ray Crystallography Reveals the Unique Position Of Cbs Domains In The Msm Gmpr Octamermentioning
confidence: 99%
“…GMPRs typically do not possess CBSs, with the exception of GMPRs from the pathogenic protozoans Trypanosoma brucei (Tb GMPR) (Bessho et al, 2016), Trypanosoma congolense (Tc GMPR) (Sarwono et al, 2017) and Leshmania donovani (Ld GMPR) (Smith et al, 2016). Recently, structural analysis of Tb GMPR showed that ATP induces octamer dissociation, while guanine nucleotides do not influence the enzyme's oligomeric state (Imamura et al, 2020).…”
Section: Introductionmentioning
confidence: 99%